2023
DOI: 10.3390/agronomy13051223
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Canopy and Belowground Phenotyping of a Set of Peanut CSSLs Detects Lines with Increased Pod Weight and Foliar Disease Tolerance

Abstract: We deployed field-based high-throughput phenotyping (HTP) techniques to acquire trait data for a subset of a peanut chromosome segment substitution line (CSSL) population. Sensors mounted on an unmanned aerial vehicle (UAV) were used to derive various vegetative indices as well as canopy temperatures. A combination of aerial imaging and manual scoring showed that CSSL 100, CSSL 84, CSSL 111, and CSSL 15 had remarkably low tomato spotted wilt virus (TSWV) incidence, a devastating disease in South Georgia, USA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…The latter utilizes a unique air-launched resistively loaded vee dipole antenna design, which had been developed as a means to detect buried objects without the necessity of ground contact [30][31][32]. The antenna array unit has been used in other published research [15,16,23,33] and is pictured in Figure 2. An air-launched antenna was used because of its greater suitability for scanning uneven agricultural surfaces with the accepted trade-offs of a strong ground return and less energy being transmitted into the soil subsurface than with a ground-coupled unit [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter utilizes a unique air-launched resistively loaded vee dipole antenna design, which had been developed as a means to detect buried objects without the necessity of ground contact [30][31][32]. The antenna array unit has been used in other published research [15,16,23,33] and is pictured in Figure 2. An air-launched antenna was used because of its greater suitability for scanning uneven agricultural surfaces with the accepted trade-offs of a strong ground return and less energy being transmitted into the soil subsurface than with a ground-coupled unit [34].…”
Section: Methodsmentioning
confidence: 99%
“…An alternative to an image analysis approach is a frequency-based analysis where the GPR signal is decomposed into its component frequencies, which are then evaluated as features predictive of biomass. Observed root biomass of cassava and peanut has been predicted using this method [16,23]. An additional alternative for GPR feature extraction is the use of wavelet methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, throughout this Special Issue, the works by Pandit et al [13], Gimode et al [20], and Burbano-Erazo et al [19], respectively illustrated in rice, peanuts, and beans, the feasibility and power to update classical introgression breeding [35] with modern 'omics' approaches, such as genomics and phenomics. This integration enables guiding more rapidly and with better precision the pyramiding of exotic variation into elite commercial backgrounds.…”
Section: Phenomics Leverage Crop Wild Gene Poolsmentioning
confidence: 96%
“…Fortunately, in this collection, two studies have harnessed cropwild diversity through phenomics. First, Gimode et al [20] studied the morphological consequences of a chromosome segment in peanuts (Arachis hypogaea) inherited from a wild relative. The authors demonstrated that this chromosome segment sources valuable trait variation from the exotic gene pool into the cultivated background.…”
Section: Phenomics Leverage Crop Wild Gene Poolsmentioning
confidence: 99%
See 1 more Smart Citation